LEGAL ANALYSIS OF THE SALE OF INHERITED FAMILY LAND - Iyam Irahatmi Kaharu; Gamar Muhdar; Arief Budiono (RADJA PUBLIKA, 2026)
This study analyzes the sale of inherited family land in Ternate City to enhance understanding of the legislative framework governing inheritance—specifically regarding legal issues arising from the sale of inherited family land that complicate the distribution of the estate. This study employs a normative-juridical legal research methodology, which involves the analysis of documents and secondary data sources such as legislation, court rulings, legal theories, and scholarly opinions. The study utilizes statutory, conceptual, and legal instrument approaches. The research findings indicate that: 1) The sale of inherited family land by a single heir without the written consent of all other heirs is null and void by operation of law. This is because the transaction violates the requirements for a valid agreement under Article 1320 of the Indonesian Civil Code as the transfer of rights to jointly owned land requires the participation of all rights holders. 2) Legal protection for aggrieved heirs can be pursued through civil litigation by filing a lawsuit in the District Court to annul the sale and transfer of rights on the grounds of an Unlawful Act pursuant to Article 1365 of the Civil Code, as well as by exercising the right to reclaim the estate as stipulated in Article 834 of the Civil Code.